Teladan Rasulullah SAW Sebagai Dasar Implementasi Sumber Daya Insani - Mushlih Candrakusuma (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Rasulullah SAW, Was a superior figure and the greatest role model in the history of humanity. The side of life is nervous with wisdom that can be studied and extracted from various dimensions of life. However, many Muslims themselves experience farsightedness, narrow in seeing their own apostles. He was only present as an apostle / prophet who deserves to be emulated by the office for affairs of mosques, madrasas and prayer rooms. Whereas his example is broader, involving human resources capable of solving socio-cultural, economic and political problems. The example will be implemented, will lead the people and achieve the vision and mission of the apostolate, namely to be a blessing for the universe, to the happiness of the world and the hereafter (falah). Keywords: Uswatun Hasanah, Character, Implementation, Human Resources